Kandungan Hormon Endogenous pada Tanaman Hortikultura - Tini, Etik Wukir; Sakhidin, S; Saparso, S; Haryanto, Totok Agung Dwi (Journal Galung Tropika, 2022)
Indonesia's flora germplasm diversity can be used as a potential source of natural growth regulators. The study's goal was to compare the auxin, cytokinin, and gibberellin content of various horticultural plant extracts: onion tubers (Allium ascalonicum), a banana weevil (Musa x paradisiaca), Moringa leaves (Moringa oleifera), sweet corn seeds (Zea mays), and green bean sprouts (Vigna radiata). The research was carried out at Jenderal Sudirman University's Research Laboratory from June 2019 to February 2020. The sample was prepared in the Chemical Laboratory of the Ministry of Agriculture's Postharvest Center in Bogor for analysis of auxin (IAA/Indole Acetic Acid), cytokinins (kinetin and zeatin), and gibberellins (GA3/ Gibberellic Acid). RAL (Completely Randomized Design) was used as the experimental design. The F test and Duncan Multiple Range Test (DMRT) were used to further examine the data. Endogenous hormone content was determined in five ingredients: shallot bulbs (Allium ascalonicum), banana hump (Musa x paradisiaca), Moringa leaves (Moringa oleifera), sweet corn seeds (Zea mays), and green bean sprouts (Vigna radiata). Moringa leaves had the highest IAA content, 662.17 ppm, according to the findings. Similarly, the highest kinetin content was found in banana weevil and Moringa leaves, with 178.82 ppm and 161.37 ppm, respectively. Shallot bulbs had the highest GA3 content, at 594.12 ppm. This demonstrates that the four plant types can be used as sources of plant hormones.